2002
DOI: 10.1892/0891-6640(2002)016<0704:eoacpw>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a 6-Month Chemotherapy Protocol with No Maintenance Therapy for Dogs with Lymphoma

Abstract: The purpose of this study was to compare a maintenance-free chemotherapy protocol based on CHOP (H from hydroxydaunorubicin = doxorubicin, O from Oncovin = vincristine) to a similar protocol with a maintenance phase for the treatment of canine lymphoma. Fifty-three dogs with multicentric lymphoma were treated with a 6-month modified version of the University of Wisconsin (UW)-Madison chemotherapy protocol (UW-25). Disease-free interval (DFI) and survival were compared to a historical control group of 55 dogs t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
276
7
9

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(319 citation statements)
references
References 14 publications
23
276
7
9
Order By: Relevance
“…In addition, 23.33% of the animals in this study were in stage V; in other studies, the percentages of animals in stage V were similar, ranging from 18 to 29% (MacEwen et al 1987, Cardoso et al 2003, though one study reported a percentage of only 4.3% (Dobson et al 2001). Studies performed in the USA evaluating the sub-stage of dogs with lymphoma showed a high percentage of dogs in sub-stage "a" (Valerius et al 1997, Chun et al 2000, Garret et al 2002. In Italy, Dobson et al (2001) reported an incidence of 49% of animals in sub-stage "a" and 51% in stage "b".…”
Section: Resultssupporting
confidence: 55%
“…In addition, 23.33% of the animals in this study were in stage V; in other studies, the percentages of animals in stage V were similar, ranging from 18 to 29% (MacEwen et al 1987, Cardoso et al 2003, though one study reported a percentage of only 4.3% (Dobson et al 2001). Studies performed in the USA evaluating the sub-stage of dogs with lymphoma showed a high percentage of dogs in sub-stage "a" (Valerius et al 1997, Chun et al 2000, Garret et al 2002. In Italy, Dobson et al (2001) reported an incidence of 49% of animals in sub-stage "a" and 51% in stage "b".…”
Section: Resultssupporting
confidence: 55%
“…Nonetheless, in numerous studies using intent-to-treat analyses, chemotherapy-related deaths are relatively rare despite frequent neutropenia. 5,6,22,23,37,41 Despite these findings, dose escalation clearly carries substantial risk and should not be used without additional research to confirm or refute the findings of this study.…”
Section: Discussionmentioning
confidence: 81%
“…[17][18][19][20][21] The exception to this rule is found in the treatment of lymphoma, for which doxorubicin-based multiagent protocols provide the longest reported survival times in both cats and dogs. 5,6,22,23 Not surprisingly, this is also the single example of an animal cancer for which 3 drug classes (ie, vinca alkaloids, alkylating agents, anthracyclines) are known to have substantial activity as single agents. [24][25][26] In addition to using multiple drugs, the maximization of dose intensity (drug dose/m 2 /wk) has proven to be of importance for improving the efficacy of chemotherapy for some human cancers.…”
mentioning
confidence: 99%
“…Treatment of all LSA phenotypes historically has involved the administration of multiagent CHOP‐based (cyclophosphamide, doxorubicin, vincristine, prednisone) chemotherapy protocols of varying length 4, 5. In addition, the use of cranial and caudal half‐body irradiation in conjunction with chemotherapy has been described for the treatment of both B‐ and T‐cell LSA 6, 7.…”
mentioning
confidence: 99%